Distribution of soft bottom sediments in the Portuguese Continental Shelf - Silva, A.J.F. (2015)
This work presents a simplified map of the spatial distribution of surficial sediments and rock outcrops along the Portuguese continental shelf in ArcGIS format. Nearly 500 samples of soft bottom shelf sediments were collected in the scope of several research projects and analyzed for grain-size. Based on the raw grain-size data, the samples were classified according to a modified version of the Folk classification system and used to create a new sediment distribution map and develop an easy-to-use GIS interface.